2016
DOI: 10.1039/c6nr02321e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic metamaterial based on the graphene split ring high-Q Fano-resonnator for sensing applications

Abstract: Structured plasmonic metamaterials offer a new way to design functionalized optical and electrical components, since they can be size-scaled for operation across the whole electromagnetic spectrum. Here, we theoretically investigated electrical active split ring resonators based on graphene metamaterials on a SiO2/Si substrate that shows tunable frequency and amplitude modulation. For the symmetrical structure, the modulation depth of the frequency and amplitude can reach 58.58% and 99.35%, and 59.53% and 97.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(50 citation statements)
references
References 45 publications
2
48
0
Order By: Relevance
“…Based on this, several notable works utilizing near-field enhancement in metallic nanostructures have been demonstrated in the mid-IR region. [157][158][159][160] Interestingly, Fano modes could www.advopticalmat.de [150][151][152] Interestingly, graphene provides an excellent 2D platform for a stable adsorption of molecules.…”
Section: Sensing and Spectroscopy Of Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this, several notable works utilizing near-field enhancement in metallic nanostructures have been demonstrated in the mid-IR region. [157][158][159][160] Interestingly, Fano modes could www.advopticalmat.de [150][151][152] Interestingly, graphene provides an excellent 2D platform for a stable adsorption of molecules.…”
Section: Sensing and Spectroscopy Of Moleculesmentioning
confidence: 99%
“…Consequently, several metamaterial-graphene hybrid device concepts have been proposed. [157][158][159][160] Interestingly, Fano modes could www.advopticalmat.de Adv. Optical Mater.…”
Section: Sensing and Spectroscopy Of Moleculesmentioning
confidence: 99%
“…Unlike the Lorentz resonance, the Fano resonance has a sharp and asymmetric line shape. Fano resonance, because of its narrow linewidth and high Q factor, can be used in biological and chemical sensors, waveguide modulators, optical switch, and slow light field [3][4][5][6][7][8][9][10], which resulted in gathering people's attention related to research [11][12][13][14][15]. To date, various metamaterial structures, ranging from microwave to optical frequencies, based on Fano resonance have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] The enhancement of the funda-mental wave and second harmonic wave has been observed in metallic structures and nanostructured metal or graphene. [24][25][26][27][28][29][30][31][32][33][34] Experiments and theories have shown that linear transmission through arrays is sensitive to many factors such as array periodicity, hole shape and size, incidence angle, and film thickness. For instance, the experimental observations of the SHG signal have also been reported.…”
Section: Introductionmentioning
confidence: 99%